Editor and Publisher : international year book : the encyclopedia of the newspaper industry : PT 1 (New York : Editor & Publisher, 2000)
"The encyclopedia of the newspaper industry."
Issued in parts, 1995-
Vols. for <2004-> issued in 3 pts: Pt.1: Dailies; Pt. 2: Weeklies (U.S. and Canada); Pt. 3: Contact directory (also called Who's where).
Vols. for <2004-> also called <84th ed.->
Issued 1920/21-1958 in Jan. as a regular number, or section of a regular number of: Editor & publisher.
Also available 1994-<1995> in a CD-ROM version, and 1995- in an online version.
SERBIB/SERLOC merged record
Keywords: Newspapers -- Directories; Journalism -- United States; Newspaper publishing -- Directories; Directories